Selective aerobic oxidation of alcohols over Au-Pd/sodium titanate nanotubes - Nepak, Devadutta; Darbha, Srinivas (Catalysis Communications, 2015)
catalytic application of Au-Pd nanoparticles supported on sodium titanate nanotubes (NaTNTs) for liquid-phase aerobic oxidation of alcohols is reported, for the first time. This reaction occurs at 80-120 degrees C, 1 atm and solvent-/alkali-free conditions yielding the corresponding carbonyls in high selectivity. This catalyst was reusable and found to be more active/selective than the corresponding monometallic Au and Pd catalysts and Au-Pd/TiO2. Higher dispersion, smaller particle size and higher amount of electron density at gold are the causes for the superior activity of Au-Pd/NaTNT catalyst. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: aerobic oxidation; Alcohol; Bimetallic Au-Pd catalyst; Sodium titanate nanotubes; TiO2